Growth, productivity and nutrient uptake of aerobic rice (Oryza sativa L.) as influenced by different nutrient management practices - Jana, Kalyan; Mondal, Ramyajit; Mallick, GK (ORYZA-An International Journal of Rice, 2020)
A field experiment was undertaken to study the effect of nutrient management on rice cv. Puspa (IET-17509) during pre-kharif season of 2013 and 2014. The experiment was conducted at Rice Research Station, Bankura with eleven different nutrient management practices i.e., N1 = N, P2O5, K2O @ 60, 30, 30 kg ha-1 (RDF);N2 = RDF + Vermicompost @ 2.5 t ha-1; N3 = RDF + FYM @ 5 t ha-1 ; N4 = FYM @ 5 t ha-1, N5 = Vermicompost @ 2.5 t ha-1 ; N6 = RDF + glyricidia (well decomposed) as green manure @ 3 t ha-1; N7 = RDF + ZnSO4 @ 20 kg ha-1 N8 = RDF + borax @ 2 kg ha-1 ; N9 = RDF + Vermicompost @ 2.5 t ha-1 + ZnSO4 @ 20 kg ha-1 ; N10 = RDF +Vermicompost @ 2.5 t ha-1 + borax @ 2 kg ha-1 ; N11 = RDF + Vermicompost @ 2.5 t ha-1 + ZnSO4 @ 20 kg ha-1 + borax @ 2 kg ha-1 respectively in randomized block design comprising of three replications. The result of experiment revealed that rice plot fertilized with the combination of NPK @ 60:30:30 + VC + ZnSO4@ 20 kg ha-1 + borax @ 2 kg ha-1 recorded the highest grain yield of 4.45 t ha-1 which was 56.69 % higher (2.84 t ha-1) than the FYM treated plot. Organic substitution by FYM and vermicompost (VC) had failed to register the significantimpact on growth, yield and nutrient uptake. Nutrient uptake and residual nutrient status was also highest in NPK @ 60:30:30 kg ha-1 + VC @ 2.5 t ha-1 + ZnSO4 @ 20 kg ha-1+ borax @ 2 kg ha-1 fertilized plot.